EVALUATION OF MEAT BYPRODUCT – SLUDGE ON COMMERCIAL BROILER CHICKEN PERFORMANCE - Sundersan, A; Babu, M; Premavalli, K; Vazhivalan, S; Pandian, C (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted for a period of six weeks to evaluate the effect of meat by-product sludge on commercial broiler performance in a total of 270 unsexed Vencobb chicks. The experimental feeds were prepared by including sludge at zero per cent (control- T1), 2 per cent (T2) and 4 per cent (T3) level in the feed. Addition of two per cent inclusion of sludge in broiler chicken diet showed significant difference in growth performance at 6 weeks of age and did not alter the serum cholesterol, triglycerides and creatinine level of broilers. Further, the profit also more in 2% inclusion of sludge.
Keywords: Meat by Product; Sludge; Broiler